2014
DOI: 10.1177/0004563214522771
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal serum concentrations of endogenous free fatty acids in newborns admitted to the neonatal intensive care unit: effects on unbound bilirubin

Abstract: Background: Few studies have reported the characterization of postnatal serum concentrations of endogenous free fatty acids (FFAs) in high-risk newborns and their effects on unbound bilirubin (UB). Methods: Serum concentrations of FFA, albumin (Alb), UB and total bilirubin (TB) were measured in 713 samples obtained within 5 days after birth from 439 newborns without intravenous lipid supplementation admitted to the neonatal intensive care unit (NICU). Serum FFA was reported as the day-specific percentile-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Serum FFAs can be increased by exogenous lipid emulsions as well as by stress. However, we recently assessed postnatal FFA concentrations and the FFA:albumin molar ratio in a large number of sick newborns who were admitted to our neonatal intensive care unit (NICU), and found that all of the patients had an FFA:albumin molar ratio <4 [18]. Because endogenous serum FFA concentrations do not affect UB concentrations, pediatricians should be aware of the potential displacing effects of FFAs in extremely preterm infants receiving >1.5 g/kg/day of exogenous, intravenous lipid supplementation [17].…”
Section: Ffasmentioning
confidence: 99%
“…Serum FFAs can be increased by exogenous lipid emulsions as well as by stress. However, we recently assessed postnatal FFA concentrations and the FFA:albumin molar ratio in a large number of sick newborns who were admitted to our neonatal intensive care unit (NICU), and found that all of the patients had an FFA:albumin molar ratio <4 [18]. Because endogenous serum FFA concentrations do not affect UB concentrations, pediatricians should be aware of the potential displacing effects of FFAs in extremely preterm infants receiving >1.5 g/kg/day of exogenous, intravenous lipid supplementation [17].…”
Section: Ffasmentioning
confidence: 99%
“…Many authors have indicated that disturbances in the serum free FAs (FFA) concentration in preterm infants could be significantly related with short-term and long-term morbidities [1][2][3]. Deposition of lipids in a fetus increases exponentially with gestational age, reaching a rate of accretion of around 7 g/day just before labor [4].…”
Section: Introductionmentioning
confidence: 99%